Effects of passengers’ anthropometry on their required comfortable seat tray table height for in-flight activities - Romli, Fairuz Izzuddin; Hamil, Muhamad Hafiz Fathullah (Aeronautical and Astronautical Society of the Republic of China, 2024)
In-flight sitting comfort is often associated with the ease of passengers in performing their in-flight activities. Subsequently, having the appropriate height of seat tray table that matches the passengers’ body anthropometry is vital in enabling them to adopt comfortable sitting posture while performing their activities. In this study, an activity-based sitting comfort experiment is conducted in an aircraft cabin mock-up where the participants were asked to rate their comfort level while using the seat tray table for eating, writing and typing activities at seven different settings of the tray table’s height. A total of 64 volunteers have participated in the experiment and the collected sitting comfort data is statistically analyzed using MINITAB software. Regression analysis is used to derive mathematical metamodel for the effects relationship between passengers’ anthropometry parameters and the required comfortable height of the seat tray table for each considered activity. The metamodel is tested for goodness-of-fit through standard testing. Overall, the metamodels for all three activities have shown good predictability with R 2 value of higher than 99%. The fitted models indicate that different activities correspond to a different comfortable seat tray table height, and this also varies for different passengers due to their different body anthropometry measurements.